2000
DOI: 10.1021/jp994022n
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Computational Chemistry to the Study of Lanthanide(III) Ions in Aqueous Solution:  Implementation and Validation of a Continuum Solvent Approach

Abstract: A set of atomic radii used for the construction of solute cavities in the framework of the polarizable continuum model (PCM) is extended and validated with the aim of supporting the investigation of lanthanide(III) complexes in aqueous solution. The parameterization of the atomic radii for the whole Ln(III) series is performed by minimizing the differences between the experimental and the calculated standard hydration free energies of the ions calculated at the HF level. The optimized radii show a remarkable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 33 publications
(40 reference statements)
10
102
1
Order By: Relevance
“…For lanthanide atoms, the previously parametrized radii were used. [37] The cavitation and dispersion nonelectrostatic contributions to the energy and energy gradient were omitted. The NMR shielding tensors of [Ln(L)(H 2 O)] À (GIAO [56] method) were calculated both in vacuo and in solution at the at the HF and DFT (B3LYP functional) [57,58] levels with the ECP of Stevens et al [44] and the 6-311G** basis set for the ligand atoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For lanthanide atoms, the previously parametrized radii were used. [37] The cavitation and dispersion nonelectrostatic contributions to the energy and energy gradient were omitted. The NMR shielding tensors of [Ln(L)(H 2 O)] À (GIAO [56] method) were calculated both in vacuo and in solution at the at the HF and DFT (B3LYP functional) [57,58] levels with the ECP of Stevens et al [44] and the 6-311G** basis set for the ligand atoms.…”
Section: Methodsmentioning
confidence: 99%
“…As there is not a good all-electron basis set for lanthanides, the effective core potential (ECP) of Dolg et al and the related [5s4p3d]-GTO valence basis set was applied in these calculations. [36] This ECP includes 46 + 4f n electrons in the core, leaving the outermost 11 electrons to be treated explicitly; it has been demonstrated that this method provides reliable results for the lanthanide±aqua ions, [37] several lanthanide complexes with polyamino carboxylate ligands, [38,39] and lanthanide dipicolinates. [40] In contrast to allelectron basis sets, ECPs account to some extent for relativistic effects, which are believed to become important for the elements from the fourth row of the periodic table.…”
Section: Ab Initio Calculations: the [Ln(l)(h 2 O)]mentioning
confidence: 99%
“…Likewise, the Sandersons EN values of Interestingly, the S Ln 3+ values linearly correlate to the atomic numbers (Z) (Figure 2 c). Among four other EN scales that have been assigned to Ln 3+ (Supporting Information, Table SI (Figure 2 e), [46] which allows us to estimate the unavailable heat of hydration for Pm 3+ to be 823.4 kcal mol À1 . The assigned S Ln 3+ values (0.154-0.773) are lower than those of AllredRochow (1.08-1.14), Pauling (1.10-1.27), Zhang (1.190-1.343), and Xue (1.327-1.479).…”
Section: +mentioning
confidence: 99%
“…These results are in line with those found in the case of other gadolinium complexes with similar ligands (DOTA or DOTMA). [23] These two parameters could be corrected by the use of a more extended basis set and the inclusion of the solvent by means of a continuous model [24] but such a calculation would be too time-consuming. Nevertheless, the overall agreement between experimental and theoretical data is good since the average deviation is only 0.05 Å for the distances and 2.2°f or the angles.…”
Section: 7ϫ18 å )mentioning
confidence: 99%